Scientific Evening: university education in favor of society (Research, Society and Development, 2023)
Objective: To describe the experience of extension workers in relation to the actions of the Entardecer Científico project in touching on the importance of health issues for the internal and external community. Methodology: This is a descriptive, reflective, qualitative study, of the experience report type, on the knowledge experienced by extension workers from the activities and actions developed in the Extension Project Entardecer Científico at the University of the State of Mato Grosso. Results: During the period from January 2021 to June 2022, 17 events were held remotely and online with transmission on YouTube due to the COVID-19 pandemic. All activities were carried out by a group of nursing students coordinated by a professor participating in the project. The team defined the theme, showed the speaker and developed all the bureaucratic and organizational parts in order to hold the lecture. After the event, the team writes the final report of the event, the scientific writing of the presentation, dissemination of results and difficulties encountered. These results will be disseminated through a simple abstract, an expanded abstract, a journal article and a book chapter. Conclusion of the study: The training of academics and health professionals through lectures is extremely important and has become even more necessary in the face of the pandemic. Participating in extension actions contributes to the promotion of knowledge sharing through lectures, expands knowledge of the health theme for students and society. Provides opportunities to work on communication skills, collaborative leadership, interpersonal relationships and teamwork.